Intervensi Multifaset dalam Peningkatan Kepatuhan Menjalani Program Pengobatan Pasien Hemodialisa - Anggriyana Tri Widianti; Diana Irawati; Dewi Anggraini; Ukim Ukim; Angga Wilandika; Inggriane Puspita Dewi (Universitas Malahayati Lampung, 2026)
ABSTRACT Hemodialysis is one of the common treatments performed by patients with CKD in Indonesia. The physical consequences of hemodialysis can affect the patient's psychology which ultimately results in non-compliance with the hemodialysis treatment program. This requires management to improve patient adherence to the hemodialysis program, namely multifaceted interventions in the form of education and cognitive behavioral therapy. This study aims to apply and prove a Multifaceted Intervention in increasing adherence of hemodialysis patients. This study was carried out on 12 hemodialysis patients intervention group and 12 patient control group. The level of adherence was measured using The End-Stage Renal Disease Adherence Questionnaire. A multifaceted intervention was provided over 3 weeks. The results of the application of EBN obtained an average pre-intervention score of 792 with a standard deviation of 126, a post-intervention score of 846 with a standard deviation of 127. Intradialytic weight gain pre-intervention 5.96 decreased to 5.39 in post-intervention, the p value of compliance was 0.002 and the p value of IDWG was 0.009. Every nursing action must be based on existing evidence so that it can improve the quality of nursing services, so it is suggested that multifaceted interventions can be used as non-pharmacological interventions for nurses to help increase adherence and reduce IDWG in hemodialysis patients. Keywords: Adherence, Cognitive Behavioral Therapy, Hemodialysis, Multifaset Intervention, Intradialytic Wight Gain. ABSTRAK Hemodialisis menjadi salah satu penatalaksanaan yang umum dilakukan oleh pasien dengan penyakit ginjal kronis di Indonesia. Konsekuensi fisik akibat hemodialisis ini dapat mempengaruhi psikologis pasien yang akhirnya berdampak pada ketidakpatuhan terhadap program pengobatan hemodialisis. Hal tersebut membutuhkan manajemen dalam peningkatan kepatuhan pasien terhadap program hemodialisis yaitu intervensi multifaset berupa edukasi dan cognitive behavioral therapy. Penelitian ini bertujuan untuk mengetahui Intervensi Multifaset dalam kepatuhan pasien hemodialisis dan intradialytic wight gain (IDWG). Penelitian menggunakan desain quasi experiment terhadap 12 orang intervensi dan 12 kontrol pasien hemodialisis. Tingkat kepatuhan diukur menggunakan The End-Stage Renal Disease Adherence Questionnaire . Intervensi multifaset diberikan selama 3 minggu. Hasil didapatkan rerata skor pre intervensi (Mean ± SD) 792±126, skor post intervensi (Mean ± SD) 846±127. Intradialytic wight gain (IDWG) pre intervensi 5,96 turun menjadi 5,39 pada post intervensi, dengan uji Wilcoxon p value IDWG yaitu 0,009 dan uji T-Test p value kepatuhan yaitu 0,002 dan Intervensi multifacet terbuti menurunkan IDWG dan meningkatkan kepatuhan pada pasien yang menjalani HD Kata Kunci: Cognitive Behavioral Therapy, Hemodialisis, Intervensi Multifaset, Kepatuhan, Intradialytic Wight Gain.